A preliminary study on the proinflammatory mechanisms of Treponema pallidum outer membrane protein Tp92 in human macrophages and HMEC-1 cells. (September 2017) - Luo, Xi; Zhang, Xiaohong; Zhao, Tie; Zeng, Tiebing; Liu, Wen; Deng, Meixia; Zhao, Feijun
Abstract: Aims: To determine proinflammatory mechanisms of Treponema pallidum outer membrane protein Tp92 in the early syphilis infection in human macrophages and HMEC-1 cells. Methods: Recombinant Tp92 protein was used to stimulate target human macrophages and HMEC-1 cells. PDTC (Pyrrolidinedithiocarbamic acid), SB202190 and Z-YVAD-FMK were used to block the MyD88/NF-κB, MAPKs/p38 and NLRP3/Caspase-1 pathway, respectively. TNF-α, IL-1β, IL-6, IL-8, NLRP3, casepase-1 were detected by ELISA or Western blot. Lactate dehydrogenase (LDH) activity was measured. Results: Tp92 protein could significantly induced the secretion of proinflammatory cytokines TNF-α, IL-1β, IL-6 and IL-8 in HMEC-1 cells, but not in macrophages except IL-8. When MyD88/NF-κB pathway was blocked, differences in the secretion of TNF-α, IL-6 and IL-1β levels and LDH enzyme activity between Tp92 group and Tp92 + PDTC group were not significant (P > 0.05) in HMEC-1 cells and macrophages except IL-8(P < 0.05). When MAPKs/p38 pathway was blocked, differences in the secretion of TNF-α, IL-1β, IL-6 and IL-8 and LDH enzyme activity both Tp92 group and Tp92 + SB2010190 group were not significant (P > 0.05) in HMEC-1 cells and macrophages. In contrast, when NLRP3/Caspase-1 pathway was blocked with Z-YVAD-FMK, TNF-α, IL-6 and IL-1β levels, LDH enzyme activity, and Caspase-1 and NLRP3 protein levels were significantly declined (P < 0.05) in HMEC-1 cells except IL-8(P > 0.05). The LDH enzyme activity in macrophages was decreased before and after Z-YVAD-FMK blocking (P < 0.05), however, differences in the secretion of TNF-α, IL-1β, IL-6 and IL-8 between Tp92 group and Tp92+Z-YVAD-FMK group in macrophages were not significant (P > 0.05). Conclusions: Tp92 protein may promote proinflammatory cytokines TNF-α, IL-1β, IL-6 secretion of HMEC-1 cells, but not in macrophages, and increase the LDH enzyme activity of HMEC-1 cells and macrophages through NLRP3/Caspase-1 pathway. However, Tp92 protein may promote IL-8 secretion of HMEC-1 cells and macrophages through MyD88/NF-κB pathway. Highlights: Tp92 protein may promote IL-8 secretion of HMEC-1 cells and macrophages through MyD88/NF-κB pathway. The LDH enzyme activity of HMEC-1 cells and macrophages may increase through NLRP3/Caspase-1 pathway. Tp92 protein may promote proinflammatory cytokines TNF-α, IL-1β, IL- 6 secretion of HMEC-1 cells, but not in macrophages.